Literature Review : Efek Suplementasi Kurkumin pada Penderita Diabetes Melitus - Andynesthi Nindya Ika Putri (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Diabetes mellitus is a condition of elevated blood glucose levels due to impaired insulin secretion, insulin resistance, or both. This disease can lead to various serious complications that impact quality of life if not properly managed. Current diabetes management generally involves dietary modification, physical activity, and antidiabetic drug therapy. However, recent research has revealed the potential of bioactive compounds from natural sources such as curcumin in minimizing the risk of diabetes-related complications. This literature review examines and analyzes research evidence on the effects of curcumin supplementation on health parameters in patients with diabetes mellitus. The review was conducted on English-language publications in the last 10 years (2014-2024) using electronic databases. The reviewed experimental and cohort studies demonstrate the influence and beneficial effects of curcumin on glycemic control, lipid profile, weight reduction, and kidney function protection in diabetic patients. Curcumin has the potential to contribute to reducing oxidative stress and inflammation as the main triggering factors for complications of diabetes mellitus.